Flax domesticationprocesses as inferred from genome-wide SNP data - Fu, Yong-Bi (Scientific reports, 2025)
Flax (Linum usitatissimum L.) is one of the founder crops domesticated for oil and fiber uses in the Near-Eastern Fertile Crescent, but its domestication history remains largely elusive. Genetic inferences so far have expanded our knowledge in several aspects of flax domestication such as the wild progenitor, the first use of domesticated flax, and domestication events. However, little is known about flax domestication processes involving multiple domestication events. This study applied genotyping-by-sequencing to infer flax domestication processes. Ninety-three Linum samples representing four flax domestication groups (oilseed, fiber, winter and capsular dehiscence) and its wild progenitor (or pale flax; L. bienne Mill.) were sequenced. SNP calling identified 16,998 SNPs that were widely distributed across 15 flax chromosomes. Diversity analysis found that pale flax had the largest nucleotide diversity, followed by indehiscent, winter, oilseed and fiber cultivated flax. Pale flax seemed to be under population contraction, while the other four domestication groups were under population expansion after bottleneck. Demographic inferences showed that five Linum groups carried clear genetic signals of multiple mixture events that were associated largely with oilseed flax. Phylogenetic analysis revealed that oilseed, fiber and winter flax formed two separate phylogenetic subclades. One subclade had abundant winter flax, along with some oilseed and fiber flax, mainly originating in the Near East and nearby regions. The other subclade mainly had oilseed and fiber flax originating from Europe and other parts of the world. Dating genetic divergences with an assumption of 10,000 years before present (BP) of flax domestication revealed that oilseed and fiber flax spread to Europe 5800 years BP and domestication for winter hardiness occurred in the Near East 5100 years BP. These findings provide new significant insights into flax domestication processes.